Direct monitoring of calcium‐triggered phase transitions in cubosomes using small‐angle X‐ray scattering combined with microfluidics. Issue 6 (27th October 2016) - Ghazal, Aghiad; Gontsarik, Mark; Kutter, Jörg P.; Lafleur, Josiane P.; Labrador, Ana; Mortensen, Kell; Yaghmur, Anan
Abstract : A combination of microfluidics with X‐ray techniques has been used to perform dynamic structural studies on nanoparticulate formulations. Abstract : This article introduces a simple microfluidic device that can be combined with synchrotron small‐angle X‐ray scattering (SAXS) for monitoring dynamic structural transitions. The microfluidic device is a thiol–ene‐based system equipped with 125 µm‐thick polystyrene windows, which are suitable for X‐ray experiments. The device was prepared by soft lithography using elastomeric molds followed by a simple UV‐initiated curing step to polymerize the chip material and simultaneously seal the device with the polystyrene windows. The microfluidic device was successfully used to explore the dynamics of the structural transitions of phytantriol/dioleoylphosphatidylglycerol‐based cubosomes on exposure to a buffer containing calcium ions. The resulting SAXS data were resolved in the time frame between 0.5 and 5.5 s, and a calcium‐triggered structural transition from an internal inverted‐type cubic phase of symmetry Im 3 m to an internal inverted‐type cubic phase of symmetry Pn 3 m was detected. The combination of microfluidics with X‐ray techniques opens the door to the investigation of early dynamic structural transitions, which is not possible with conventional techniques such as glass flow cells. The combination of microfluidics with X‐ray techniques can be used for investigating protein unfolding, for monitoring the formation of nanoparticles in real time, and for other biomedical and pharmaceutical investigations.